Comparative study of urea-15N fate in pure bamboo and bamboo-broadleaf mixed forests - Wu, Yiyuan; Dong, Wenyuan; Zhong, Huan; Duan, Jixia; Li, Weidong; Pu, Chan; Li, Xin; Xie, Zexuan (Frontiers in Plant Science, 2024)
Bamboo is a globally significant plant with ecological, environmental, and economic bene-fits. Choosing suitable native tree species for mixed planting in bamboo forests is an effective measure for achieving both ecological and economic benefits of bamboo forests. However, little is currently known about the impact of bamboo forests on nitrogen cycling and utilization efficiency after mixing with other tree species. Therefore, our study aims to compare the nitrogen cycling in pure bamboo forests with that in mixed forests. Through field experiments, we investigated pure Qiongzhuea tumidinoda forests and Q. tumidinoda-Phellodendron chinense mixed forests, and utilized 15N tracing technology to explore the fertilization effects and fate of urea-15N in different forest stands. The research findings reveal that in both forest stands, bamboo culms account for the highest biomass percentage (42.99%-51.86%), while the leaves exhibited the highest nitrogen concentration and total nitrogen uptake (39.25%-44.52% / 29.51%-33.21%, respectively) Additionally, the average nitrogen uptake rate of one-year-old bamboo is higher (0.25 mg kg-1 a-1) compared to other age groups. The urea-15N absorption in mixed forests (1066.51-1141.61 g ha-1, including 949.65-1000.07 g ha-1 for bamboo and 116.86-141.54 g ha-1 for trees) was significantly higher than that in pure forests (663.93-727.62 g ha-1, P＜0.05). Additionally, the 15N recovery efficiency of culms, branches, leaves, stumps, and stump roots in mixed forests was significantly higher than that in pure forests, with increases of 43.14%, 69.09%, 36.84%, 51.63%, 69.18%, 34.60%, and 26.89%, respectively. The recovery efficiency of urea-15N in mixed forests (45.81%, comprising 40.43% for bamboo and 5.38% for trees) and the residual urea-15N recovery rate in the 0-60 cm soil layer (23.46%) are significantly higher compared to those in pure forests (28.61%/18.89%). This could be attributed to the nitrogen losses in mixed forests (30.73%, including losses from ammonia volatilization, runoff, leaching, and nitrification-denitrification) being significantly lower than those in pure forests (52.50%). These findings suggest that compared to pure bamboo forests, bamboo in mixed forests exhibits higher nitrogen recovery efficiency, particularly with one-year-old bamboo playing a crucial role.